Longitudinal growth of very low birth weight neonates during first year of life and risk factors for malnutrition in a developing country. (22nd January 2013) - Mukhopadhyay, Kanya; Mahajan, Rama; Louis, Deepak; Narang, Anil
Abstract Aims To study growth of very low birth weight neonates (VLBW) during first year and identify risk factors for malnutrition. Methods Neonates ≤34 weeks and ≤1500 g enrolled in a human milk fortification trial were prospectively followed till 1 year corrected age (CA). Anthropometry was plotted on WHO charts. Risk factors were compared between well nourished and underweight infants. Results One hundred and thirty‐two, 127, 110, 99 and 101 neonates were followed at CA of 40 weeks, 3, 6, 9 and 12 months. Weight (Mean Z score −2.3 ± 1.2 to –1.7 ± 1.4; p = 0.005) and length (−2.1 ± 1.5 to –1.5 ± 1.3; p = 0.004) improved significantly, from 40 weeks to one year while head circumference declined (−0.92 ± 1.1 to –1.2 ± 1.1; p < 0.001). Incidence of underweight, stunting, microcephaly and wasting changed from 63%, 53%, 13% and 52% neonates at 40 weeks to 41%, 32%, 21% and 27% at one year. Growth between fortified and unfortified or small for gestational age (SGA) and appropriate for gestational age (AGA) groups were similar, while extremely low birth weight (ELBW) neonates showed poorer growth. Z score of weight at 3 months emerged as an independent predictor of malnutrition at one year. Conclusion VLBW neonates, especially the ELBW group remained growth retarded at CA of one year. Z score of weight at 3 months was a significant risk factor for malnutrition at one year.